Validade, reprodutibilidade e valores de referência do teste de degrau de seis minutos - Arcuri, Juliano Ferreira (Universidade Federal de São Carlos, 2012)
Background: Six minute Step Test, like other clinical exercise test is an important tool to evaluate the physical capacity, as being simpler and less expensive, however it doesn t have reference values and its reproducibility wasn t evaluated in apparently healthy population. Objectives: The objective of this study was to determine the reproducibility of the test in apparently healthy population and develop an equation to predict reference values for the Brazilian population. Methods: apparently healthy individuals, older than 18 years, were evaluated for anthropometry, body composition, lung function, physical activity level, it was conducted two step test and two Six Minute Walk Test. We investigated the relationship between the demographic and anthropometric findings and with performance in the clinical exercise tests. The reproducibility was assessed by intraclass correlation coefficient and standard error of measurement. It was used the stepwise method, in the multiple regression analysis, to develop an equation model to predict reference values. Results: 91 subjects (40 men) were included in this study, with an average performance in the first and second test step of 134 steps. Correlations were found between the Step Test and age, height, length of lower limbs and body fat percentage. The two clinical exercise tests were excellently reproducible, with ICI> 0.8. We developed a regression equation (p <0.05 and R ² = 0.5): Six Minute Step Test=348.4 + 48.48 x Gender (male = 1, female = 0) -1.29 Age(years) -0, 98xHeigth (cm). Conclusions: The test step is reproducible in apparently healthy individuals and there is a relationship with height, age and gender thar can predict reference values for the Brazilian population
Keywords: Fisioterapia; Fisiologia do exercício; Teste de esforço; Doença Pulmonar Obstrutiva Crônica (DPOC); CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL